Soil liquefaction hazard assessment along shoreline of Peninsular Malaysia / Huzaifa Hashim - Huzaifa, Hashim (2017)
The thesis provides a complete liquefaction potential hazard study for shoreline of 1972 km covering 40 shoreline districts of 11 major states of Peninsular Malaysia. Two main aspects are considered in defining soil liquefaction study which consists of regional geotechnical settings and regional seismicity information. 4 interrelating approaches are introduced in study; soil liquefaction screening, cyclic triaxial testing, earthquake study and liquefaction hazard mapping. In this study, governing factors contributing to soil liquefaction hazard were selected and adapted in soil liquefaction screening in highlighting soil liquefaction potential areas. The cyclic loading was applied on sand and clay samples to establish the shear modulus reduction curves and damping ratio curves that represents regional soil performance for seismic response. Probabilistic seismic hazard analysis (PSHA), spectrum matching procedure (SMP) and site response analysis (SRA) was adapted in seismic study in generating ground motion of studied sites. Soil liquefaction assessment approach based on Simplified Procedure was used in developing the hazard map for shoreline of Peninsular Malaysia. A mitigation chart is also introduced the in the study as a precursory measure in promoting safe built environment in the region. Findings revealed that shoreline area consist of vulnerable conditions to soil liquefaction hazard. The ground motion generated presents high amplification factor on the east coast region of Peninsular Malaysia specifically in the state of Terengganu and Kelantan. In general, the hazard map produced indicates that shoreline areas are vulnerable to soil liquefaction hazard. This soil liquefaction study will contribute towards promoting preparedness and enhanced awareness in the changing environment in today‘s context.